ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN PADA FASHION WEAR - Sitorus, Resky Ananda; Silalahi, Mesri (Computer Science and Industrial Engineering, 2023)
The sales business field is indeed interesting to be pursued, not only for companies or organizations, but also by the wider community who are trying hard to develop businesses in this field. However, often their hard efforts to increase sales are not matched by the use of good information systems, causing several problems to arise.This problem arises because many organizations or companies still rely on conventional systems in various processes such as ordering goods, processing data, storing data, and preparing sales reports. To provide satisfactory service to customers and produce accurate information, Bs Collection Stores really need a computerized information system and good data processing. Therefore, it is necessary to design and build a sales information system that uses a MySQL database. The method used in designing and building this system is the Software Development Life Cycle (SDLC). By using the SDLC method, the process of designing and implementing a sales system, especially at Bs Collection Stores, will become more structured, planned and efficient, so that problems can be overcome. It is hoped that the problems faced by Bs Collection Stores can be properly resolved through the use of a computerized sales information system and the SDLC method.